Stainless Steel Bridge Girders with Corrugated Webs - A parametric study to investigate the sensitivity of Stainless steel girder’s shear behaviour to intial imperfection - Mohra, Naheel; Hlal, Fatima (My University, 2021)
Steel bridges are prone to corrosion, and over the lifetime of the bridge, corrosion is likely to necessitate maintenance work, re-painting, and inspections. Stainless steel, on the other hand, is more corrosion-resistant material and can help to reduce the problem’s negative impacts. Moreover, as these structures are deep in web height, it is common to use thin webs in steel bridges to prevent utilizing a lot of material and get the highest strength out of the material with a minimal amount of weight. The method of manufacturing, however, is complicated due to the thin thickness. To overcome this problem, corrugated webs, which are lighter than traditional flat web steel girders, are used. This kind of Thin shell element, on the other hand, is susceptible to initial imperfection. The aim of this master’s thesis is to research the shear behavior of bridge gird ers with stainless steel corrugated webs and their sensitivity to initial imperfection. This is done by, firstly, a literature review to decide the most influential parame ters on the shear capacity of bridge girders with corrugated webs. Secondly, using ABAQUS software, a sensitivity analysis to initial imperfection is investigated by varying the shape and amplitude of initial imperfection on three different girders. Single eigen shapes and various combinations of eigen shapes have been considered as the shape of the initial imperfection. Hw/400, Hw/300, Hw/200, and Hw/100 are used to estimate the amplitude. Thirdly, a limited parametric study, by changing one-factor-at-a-time, has then been performed to see the effect of each dimensional parameter on the girder’s shear capacity. Finally, the shear capacity of the in vestigated girders has been compared to the shear capacity provided by Eurocode equations. The results show that the shear capacity of bridge girders with stainless steel corru gated webs is sensitive to both initial imperfection shape and amplitude. The shear capacity decreases significantly with increasing initial imperfection amplitude. In addition, the most critical initial imperfection shape is a single-mode shape of Eigen shapes and not the first positive mode shape. Web height, web thickness and cor rugation depth significantly increase the shear capacity. Flat fold length decreases the shear capacity. However, the shear span has a negligible effect. Finally, using the design curve of Eurocode with the first buckling mode and initial imperfection amplitude of Hw/200 is on the safe side.
Keywords: Corrugated web, Shear capacity, Stainless steel, Steel bridges, Initial imperfection; Sensitivity analysis, Parametric study